2017
DOI: 10.14302/issn.2575-1212.jvhc-17-1555
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Contagious Bovine Pleuropneumonia in Khartoum State, Sudan

Abstract: The study was carried out to investigate the occurrence of contagious bovine pleuropneumonia CBPP in Khartoum state. One-hundred twenty-two pneumonic lung tissue samples were collected from different slaughterhouses (116 samples most of which from local breed cattle) and from the field (six samples from cross breed cattle). Two-hundred and fifty-seven serum samples were collected randomly from cattle in different areas of the state. Tissue samples were cultivated using the standard mycoplasma procedures.Mmm wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
1
2
0
3
Order By: Relevance
“…Furthermore, this was a statistically significant (0.0001) p < 0.05 of the effect between disease prevalence and breed. As reported in previous studies, European breeds and their crosses are more susceptible to the disease than local African breeds [12]. This study found the highest sero-prevalence of contagious bovine pleuropneumonia in cattle with poor body condition (22.2%) compared to those with medium (11.1%) and good body condition (2.2%).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, this was a statistically significant (0.0001) p < 0.05 of the effect between disease prevalence and breed. As reported in previous studies, European breeds and their crosses are more susceptible to the disease than local African breeds [12]. This study found the highest sero-prevalence of contagious bovine pleuropneumonia in cattle with poor body condition (22.2%) compared to those with medium (11.1%) and good body condition (2.2%).…”
Section: Discussionsupporting
confidence: 75%
“…Contagious bovine pleuropneumonia transmission occurs through direct and repeated contact between infected and sus-Open Journal of Veterinary Medicine ceptible animals. Inhalation of infective droplets is the main route of infection [12]. This disease is endemic in Africa, although it has been eradicated in other parts of the world through the application of restrictions to the movement of cattle as well as test and slaughter policies combined with compensation for livestock owners during the mid-20th century [13].…”
Section: Introductionmentioning
confidence: 99%
“…Também foram observadas áreas de fibrose, acompanhadas por uma infiltração generalizada de linfócitos e espessamento dos septos interalveolares. Estes achados estão de acordo com a literatura (GIZAW, 2004;KARAM et al, 2005;KOCK et al, 2015), incluindo um estudo com a análise histopatológica em 108 seções de pulmões de animais com a PPCB, confirmados pela sorologia (KARAM et al, 2005).…”
Section: Discussionunclassified
“…Ainda, foi identificado enfisema pulmonar em 34% nos animais do nosso estudo. Apesar de não serem as características clássicas da infecção pelo MmmSC, outros estudos também descrevem esses achados na doença (KARAM et al, 2005;KOCK et al, 2015). Do mesmo modo, observamos que 4% dos animais apresentaram vasculite, característica observada também em infecções experimentais em bovinos (KOCK et al, 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation